Komunikasi Interpersonal Dakwah Rosulullah Dalam Perspektif Hadist - Siti Saada; Akhda Marza Indra (STAI Bumi Silampari, 2022)
This paper describes the hadith perspective on how the Prophet's interpersonal communication in preaching. Interpersonal communication is communication carried out by two or more people to achieve a goal. In the context of the Prophet's da'wah, interpersonal communication is the strategy of the Prophet in conveying his da'wah. The da'wah that was started by the Prophet in secret until it finally arrived at the da'wah had to be carried out openly and was able to be accepted by the people of Mecca at that time, showing that the Prophet had the power to convey the da'wah, so that what he conveyed was able to make the people of ignorance at that time to want to worship God. In addition to the story of the preaching of the Prophet Muhammad in the Qur'an, we can also see many hadiths which explain how the power of the Prophet's preaching was in responding to irregularities during the Jahiliyyah period. So the key to the success of the Prophet's da'wah is the interpersonal communication that the Prophet did with his man's.